EDUCATIONAL AND CULTURAL POTENTIAL OF INCLUSIVE COMICS - Derkachova, Olga; Tytun, Oksana; Ushnevych, Solomiya (Mountain School of Ukrainian Carpaty, 2022)
The article deals with the research on comics' educational and cultural potential, particularly inclusive comic books, and their influence on inclusive culture formation. Inclusive graphic stories have long been part of the readership abroad. Gradually, this tradition is becoming popular in the Ukrainian cultural space. The chronology of the implementation of inclusive education in Ukraine is established, a brief overview of the regulatory framework is given. There is more and more inclusive literature on the Ukrainian book market: it is both translations and works of domestic writers, it is literature for the youngest, teenagers, adults, and it is fiction and nonfiction. In 2019 the first inclusive comic book "Friends 2.0" appeared. It was published with the support of the Ukrainian Cultural Foundation within the framework of the Inclusive Art program. The comic book "Friends 2.0" is an illustrative material for the analysis. The given research identifies the features of inclusive literature and clarifies its role in forming a tolerant society. The main evolutionary steps of comics are conveyed (Egyptian drawings in the burial chambers, "Ocelot's Claw", The Bayeux Tapestry, William Hogarth’s caricatures, stories in drawings by Rodolphe Töpffer, "Max und Moritz" by Wilhelm Busch, "The Yellow kid" by Richard Outcault and others). The basic terms and concepts of comic book culture are explained, taking into account the specifics of their translation. The history of Ukrainian comics is written daily, undergoes great changes, forms the main slogans and ideas in which it operates and develops. Currently, Ukrainian comics are established as a separate literary and art genre. Inclusive "Friends 2.0". comics are five stories based on real events. Every story is a story of struggle and victory. These are the first inclusive stories in the Ukrainian cultural space. They proclaim that everyone in the world is important, that disability is not a sentence, the importance of adaptation and inclusion, faith and dreams that come true. The article highlights the structural and semantic components of the stories in the comic book "Friends 2.0", analyzes the role of the motto in the content of the stories of this book, the background of panels, characters, and more. The analysis of inclusive comic strips as achievements of comic book culture and as examples of graphic texts in which the inclusive component dominates is offered. It helps to identify a special type of superhero in "Friends 2.0". The educational potential of such comics and their influence on the context of inclusive culture are identified. Keywords: inclusive literature, inclusive comics, comic book, diegesis, narrative, encapsulation, motto, superhero.